The Junta da Instituição Vaccinica da Corte do Rio de Janeiro: The Fight Against Smallpox in Brazil During the Joanine Period (Ágora Journal, 2024)
The study examines the process of smallpox vaccination in Brazil, in the Johannine period from 1808 to 1820. This period was crucial for the institutionalization of the practice in the country following the creation in 1811 of the Junta da Instituição Vaccinica da Corte do Rio de Janeiro, an institution that He acted mainly in vaccinating the enslaved population of Brazil. The main sources for this study were the newspaper Gazeta do Rio de Janeiro, in which we observed the publication of monthly data on vaccination in Rio de Janeiro and the documents of the Junta itself, where it is possible to observe the records of vaccinated people, conservation methods, reports on the deaths caused by smallpox, among others. We realized that the institution was successful in maintaining and increasing the number of people vaccinated at the court during the period, being decisive in maintaining and disseminating this medical practice in Brazil.
Keywords: vaccine; smallpox; slavery.